040. Survival Rate of Colorectal Cancer Patients at Dr. Zainoel Abidin General Hospital 2021-2023 - Romi, Romi (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical Education, 2024)
Background : Cancer is one of the most common cause of mortality worldwide. From the statistic, the mortality case of the Colorectal Cancer increases over 77% a year. In indonesia, the incidence of Colorectal Cancer was high. However, profile data and survival rates are still rarely reported in Indonesia, especially Aceh. The aim of this study were to determine the survival rate of Colorectal Cancer patients and also to obtain the profile data based on age, gender and clinical categories in Dr. Zainoel Abidin Hospital, Aceh Indonesia. Methods : This study was an observational descriptive study with a cross-sectional approach. The data used in this study is patient's medical record according to the inclusion criteria, using 104 medical records of Colorectal Cancer patients for the period 2021-2023. Data were analyzed with univariate data analysis by SPSS. Results : Among 104 Colorectal Cancer patients, man were the most frequent demographical findings. There is (80,8%) CRC occur at age more than 40 years and most of the patients diagnosed in stage 4. Survival rate of Colorectal Cancer patient on this study mostly more than 1 year. Conclusion: The conclusion of this study is that gender, the age of patient and the Cancer stage have a significant relationship each other and also influenced the survival rate of patients.